EUS-guided 22-gauge fine needle biopsy versus single-incision with needle knife for the diagnosis of upper gastrointestinal subepithelial lesions: a randomized controlled trial - Omid Sanaei; Glòria Fernández-Esparrach; Carlos De La Serna-Higuera; Silvia Carrara; Vivek Kumbhari; Mohamad H. El Zein; Amr Ismail; Angels Ginès; Oriol Sendino; Andrea Montenegro; Alessandro Repici; Daoud Rahal; et al. (Endoscopy International Open, 2020)
Background and study aims EUS-FNA has suboptimal accuracy in diagnosing gastrointestinal subepithelial tumors (SETs). EUS-guided 22-gauge fine needle biopsy (EUS-FNB) and single-incision with needle knife (SINK) were proposed to increase accuracy of diagnosis. This study aimed to prospectively compare the diagnostic accuracy and safety of EUS-FNB with SINK in patients with upper gastrointestinal SETs. Patients and methods All adult patients referred for EUS evaluation of upper gastrointestinal SETs ≥ 15 mm in size were eligible for inclusion. Patients were randomized to undergo EUS-FNB or SINK. Lesions were sampled with a 22-gauge reverse beveled core needle in the EUS-FNB group and by a conventional needle-knife sphincterotome and biopsy forceps in the SINK group. Patients were blinded to the technique used. The primary outcome was diagnostic accuracy. Secondary outcomes included adverse events, histological yield and procedure duration. Study enrollment was terminated early due to poor recruitment. Results A total of 56 patients (31 male (55.37 %); mean age, 67.41 ± 12.70 years) were randomized to either EUS-FNB (n = 26) or SINK (n = 30). Technical success was 96.15 % and 96.66 %, respectively. The majority of lesions were gastrointestinal stromal tumors (51.78 %). No significant difference was found between EUS-FNB and SINK in terms of diagnostic accuracy for a malignant or benign disease (76 % vs. 89.28 %, respectively; P = 0.278). The rate of adverse events (none severe) was also comparable (7.69 % vs. 10 %, respectively; P = 1.0) including two abdominal pain episodes in the EUS-FNB group compared to two delayed bleeding (one requiring hospitalization and radiologic embolization) and 1 abdominal pain in the SINK group. Conclusion EUS-FNB and SINK are equally effective techniques for upper gastrointestinal SETs sampling. SINK can be associated with mild to moderate delayed bleeding.